The Supply Chain Management Influencing the efficiency of the Fruit and Vegetable Import Business from China - Hehui, Lan; Tanaborworpanid , Nutpatsorn; Veerayannon, Kietchai (International Journal of Multidisciplinary in Management and Tourism, 2024)
This article aims to (1) compare the performance of the fruit and vegetable import business from China, classified by business characteristics, and (2) study the supply chain management factors affecting the performance of the fruit and vegetable import business from China. The sample group consisted of entrepreneurs in the fruit and vegetable import business from China. The sample size was determined using the Krejcie & Morgan table with a 95% confidence level, resulting in a total of 217 participants. The data collection tool was a questionnaire, and data analysis employed descriptive statistics and content analysis. The research findings indicated that (1) there were statistically significant differences at the .05 level in the performance of the fruit and vegetable import business from China, classified by the duration of business operation. (2) Supply chain management factors affecting the performance of the fruit and vegetable import business from China collectively explained 66.00% of the overall business performance (Adj. R² = .660). The factors were ranked by influence as follows: returning, planning, and making. (Beta = .222, Sig. = .004),